CORPORATE CULTURE AS A PERFORMANCE FACTOR OF INNOVATION ACTIVITY - Pervakova, Elena (Revista Inclusiones, 2020)
The present study analyses the importance of how a company forms an innovation-oriented corporate culture in order to support the development and implementation of various types of innovations. The study aims at summarizing the approaches presented in foreign scientific literature and practical activity in order to describe the influence of certain corporate culture factors on the innovation activity of companies. The research set and solved the problem of identifying these factors, as the corporate culture has a key impact on the innovation activity of employees for Russian companies in various fields of activity. The research was conducted in two stages. The first stage consisted in several focus groups held with experts and personnel managers of various companies in order to form a preliminary list of characteristics of the corporate culture that affect the innovation activity of employees. The second stage included a questionnaire survey of owners, managers, and employees of 104 Russian companies, students of MBA programs of the Russian Presidential Academy of National Economy and Public Administration. The research identified three most important factors: understanding the goals and the mission of the company in terms of public benefit, the just approach in assessing the work of innovators and a constructive, friendly atmosphere within the company. The analysis of the correlation between the choice of factors and such respondents’ characteristics as the size and type of activity of their companies, the status of the respondent in the hierarchy of the company was conducted with the use of methods of categorial analysis and calculations of Yule’s measure to show the connection between nonnumeric characteristics. According to the results of the survey, there was no significant correlation between the respondents’ answers and different demographic characteristics of the companies, and therefore, it was recommended to reduce the number of factors. The results of the survey suggest the conclusion that commitment to public benefit and increase of activity awareness are main motives for innovation creativity.